Longitudinal relationship between depression and antisocial behaviors in Korean adolescents - Kim, Na Ri; Jo, Yeong Seon; Cho, Young Il; Choi, Younyoung; Park, Sang Jin (Frontiers in Psychiatry, 2023)
Background: It is well known that depression and delinquency in adolescents are highly correlated, but longitudinal studies on the causal relationship between them are not active in East Asia compared to in Western culture. In addition, even the results of research on causal models and sex differences are inconsistent. Objectives: This study examines the longitudinal reciprocal effects between depression and delinquent behavior in Korean adolescents based on sex differences. Methods: We conducted multiple-group analysis by using an autoregressive cross-lagged model (ACLM). Longitudinal data from 2,075 individuals (2011–2013) were used for analysis. The longitudinal data are from the Korean Children and Youth Panel Survey (KCYPS), and data were used beginning with students at 14 years old (in the second grade of middle school) and tracked them until they were 16 (in the first grade of high school). Results: Boys’ delinquent behaviors at 15 years (the third grade of middle school) affected their depression at 16 years (the first grade of high school). In contrast, girls’ depression at 15 years (the third grade of middle school) influenced their delinquent behaviors at 16 years (the first grade of high school). Discussion: The findings support the failure model (FM) among adolescent boys and the acting-out model (ACM) among girls. The results imply that strategies to effectively prevent and treat delinquency and depression in adolescents must consider sex effects.